The Impact of Gender Role Norms on Mothers' Labor Supply - Danilo Cavapozzi; Marco Francesconi; Cheti Nicoletti (Institute of Labor Economics (IZA), 2021)
We study whether mothers' labor supply is shaped by the gender role attitudes of their peers. Using detailed information on a sample of UK mothers with dependent children, we find that having peers with gender-egalitarian norms leads mothers to be more likely to have a paid job and to have a greater share of the total number of paid hours worked within their household, but has no sizable effect on hours worked. Most of these effects are driven by less educated women. A new decomposition analysis allows us to estimate that approximately half of the impact on labor force participation is due to women conforming gender role attitudes to their peers', with the remaining half being explained by the spillover effect of peers' labor market behavior. These findings suggest that an evolution towards gender-egalitarian attitudes promotes gender convergence in labor market outcomes. In turn, a careful dissemination of statistics on female labor market behavior and attitudes may accelerate this convergence.
Keywords: J12; J16; J22; J24; J31; Z13; 330; culture; norms; gender; identity; peer effects